Saccadic Velocity in the New Suppression Head Impulse Test: A New Indicator of Horizontal Vestibular Canal Paresis and of Vestibular Compensation - Shen, Qiwen; Magnani, Christophe; Sterkers, Olivier; Lamas, Georges; Vidal, Pierre-Paul; Sadoun, Julien; Curthoys, Ian S.; de Waele, Catherine (Frontiers in Neurology, 2016)
Objective To determine whether saccadic velocity in the suppression head impulse paradigm (SHIMP) test is a reliable indicator of vestibular loss at the acute and at the chronic stage in patients suffering from different vestibular pathologies. Methods 35 normal subjects and 57 patients suffering from different vestibular pathologies associated with unilateral vestibular loss (UVL) or bilateral vestibular loss (BVL) were tested in the SHIMPs paradigm. SHIMPs were performed by turning the head ten times at high velocities to the left or right side, respectively. The patients were instructed to fixate on a red spot generated by a head-fixed laser projected on the wall. In this SHIMPs paradigm, healthy subjects made a large anti-compensatory saccade at the end of the head turn (a SHIMP saccade). The peak saccadic velocity, the percentage of the trials completed with saccades in ten trials, and the latency of the saccades were quantified in each group. A video-head impulse test (v-HIT) was systematically performed in all of our subjects as well as a caloric test. The DHI questionnaire was also given to chronic UVL and BVL patients. Results At the acute stage after a complete unilateral vestibular loss, patients had zero or a few anti-compensatory saccades for low velocity head turns towards the lesioned side. These saccades had lower velocity than the anti-compensatory saccades recorded during head rotation towards the intact side and /or compared to the saccades measured in control subjects. At the chronic stage, some of the patients recovered the ability to perform SHIMP saccades at each head turn towards the lesioned side but very often these saccades were of significantly lower velocity. In BVL patients, no anti-compensatory saccades or only significantly smaller ones, could be detected for head turns to both sides. Conclusion SHIMP is a specific and sensitive test to detect a complete horizontal canal loss at the acute stage. In addition, it reflects the ability of patients with moderate HVOR gain decrease to generate anti-compensatory saccades in the chronic stage. In association with v-HIT, it allows determination of the residual vestibular function and to detect anti-compensatory saccades.